If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + x + x = 8x + -7 Combine like terms: x + x = 2x 11 + 2x = 8x + -7 Reorder the terms: 11 + 2x = -7 + 8x Solving 11 + 2x = -7 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 11 + 2x + -8x = -7 + 8x + -8x Combine like terms: 2x + -8x = -6x 11 + -6x = -7 + 8x + -8x Combine like terms: 8x + -8x = 0 11 + -6x = -7 + 0 11 + -6x = -7 Add '-11' to each side of the equation. 11 + -11 + -6x = -7 + -11 Combine like terms: 11 + -11 = 0 0 + -6x = -7 + -11 -6x = -7 + -11 Combine like terms: -7 + -11 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| -10-12x=-11x+13 | | -10(1-2k)=-5(k-3) | | w-7b=y | | -32+11x=10+8x | | -67+3x=-7x+83 | | -5n-8(7n)=-8 | | (x^2)-kx+196=0 | | -168-x=53+12x | | 18x^2+18x-24=0 | | 4(5x+10)=4(x-6) | | 12x^2-204x+630=0 | | 7x-36=48+11x | | 7+n-2=-5-n | | -16-12x=40-8x | | p+2=-2-3p | | -4p+7=7-4p | | x-77=35-6 | | 2X^2-34X+105=0 | | 0=2m+5m | | 11x-6=-39 | | 15=m-4m | | p-5-3=-9 | | 3x-7+x=10 | | -12=-5b-b | | 2(x+1)-4=5x-3(2+x) | | 7x-114=40-4x | | 9x-5x+3x-x+16=22 | | 42=28-12x | | (x^2)+6=8x | | -63-4x=135+7x | | 8=4-3b+1 | | 500+35*X=55*x |